The Role of Privacy Regulation Mechanisms for Malay Families Living in Terrace Housing Towards Obtaining Optimum Muslim Visual Privacy (MVP) - Azhani Abd. Manaf; Zaiton Abdul Rahim (Allied Business Academies, 2024)
Volume 27, Special Issue 5, 2021